Impact of Habitat on Insect Pollinator Diversity on Coriander (Coriandrum sativum L.) Bloom - Devi, Manju; Sharma, Harish K.; Sharma, P. L.; Rana, Kiran (International Journal of Bio-resource and Stress Management, 2016)
The study was conducted at Pandah farm and Khaltoo farm of seed technology and production centre, Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni, Solan Himachal Pradesh, India during 2012−2013 to find out the impact of habitat on insect pollinator diversity on coriander (Coriandrum sativum L.) bloom. The survey was conducted at two different habitats, in habitat 1, field was surrounded by cultivable crops while, in habitat 2, field was surrounded by natural vegetation. Insect pollinators were identified and the Shannon–Weiner diversity index was used to measure their diversity. The diversity of insects by different sampling methods (fluorescent pan traps, scan sampling and sweep net capture) showed that more insects were observed in coriander field surrounded by natural vegetation (habitat 2) as compared to field surrounded by cultivable crop (habitat 1). Thirty nine insects belonging to 31 genera under 18 families and 8 orders were observed in the experimental habitats surrounding coriander crop. Pollinator diversity indices compared for different sampling methods in both the habitats showed different trends. The pollinator diversity indices and eveness amongst the various groups was higher in habitat 1. Richness (H max) was same in both the habitats in all sampling methods indicating that the insect visitors groups were homogenous in the two habitats for individual sampling method. Different Shannon Weiner pollinator diversity indices for different sampling methods indicated that for sampling pollinator diversity all the methods have to be collectively employed as no single method is fully reliable.